Intercultural Communication of the National Integration Forum in Maintaining Local Harmony - Muhammad Nazar Luthfi Tambunan; Rubino Rubino; Farhan Indra; Ahmad Sujai Tanjung (Ali Institute of Research and Publication, 2026)
This study examines the intercultural communication strategies used by the Forum Pembauran Kebangsaan of North Tapanuli Regency in maintaining local-wisdom-based harmony. North Tapanuli is a multicultural region shaped by ethnic, religious, and cultural diversity, making intercultural communication important for sustaining social cohesion. This study used a qualitative phenomenological approach involving twelve informants selected through purposive sampling. Data were collected through interviews, observation, and documentation, and were analyzed thematically. The findings indicate two main strategies. First, the Forum Pembauran Kebangsaan internalizes local cultural values, such as Dalihan Na Tolu, ojo adigang adigung adiguna, and dima bumi dipijak disinan langik dijunjuang, as shared ethical references in cross-cultural relations. Second, the forum applies inclusive and adaptive dialogue by involving community, religious, traditional, and government actors. Supporting factors include shared local values, stakeholder involvement, and government support, while obstacles include hoaxes, sensitive ethnicity-religion issues, limited funding, and low youth participation. Practically, the study suggests that local wisdom can serve as a communication basis for strengthening dialogue, preventing social misunderstanding, and guiding more participatory harmony programs in multicultural communities.